Information on the genotypes from the wheat crossing block of CNPT in 1990 - dos Anjos e Silva, Sérgio; N. A. de Sousa, Cantídio; F. Sartori, João; C. Medeiros, Milton; I. Linhares, Walesca; P. Gomes, Edar (Pesquisa Agropecuaria Brasileira, 1998)
The Embrapa-Centro Nacional de Pesquisa de Trigo (CNPT) develops germplasm for several wheat regions in Brazil where cropping systems, environmental conditions, and other factors are different. A great genetic variability is needed in order to reach this objective. Such variability is sought by surveying both national and foreign wheat. The objective of present study is to provide information on the genotypes used in crosses in 1990 relating to disease reactions (stem rust, leaf rust, powdery mildew, scab, and soil borne mosaic virus), reaction to aluminum toxicity, and plant traits (height, cycle, culm diameter, spike length, number of fertile tillers, and number of fertile spikelets), and information on the crosses. The crossing block consisted of 264 genotypes from Brazil and from other 15 countries. Sowing took place at two planting dates in the experimental field of CNPT and the reaction to rust races and to powdery mildew was assessed in the greenhouse. The highest values were found in the following genotypes: PF 85159 (tiller number), Tivoli and Triticale BR 4 (culm diameter), IPF 54835 (spike length), and Triticale BR 4 (number of fertile spikelets). Cultivars PF 84491, PF 85202, PF 859238, PF 87167, PF 87373, PF 87509, PF 87915, PF 892, and Triticale BR 4 showed resistance to all tested races of leaf rust and stem rust as well as to powdery mildew.